Incidencia de la Cartera Vencida Sobre el Patrimonio en la Cooperativa de Ahorro y Crédito “”Santa Rosa de Patután”, Ubicada del Cantón Latacunga, Provincia de Cotopaxi, en el segundo semestre del año 2016 - Aimacaña Yánez, Katherine Yajaira (2017)
The present research was carried out at "Santa Rosa de Patután Ltda." Savings and Credit Cooperative, It is located in Eloy Alfaro Parish, Latacunga Canton, Cotopaxi Province, the main active focus of the business is the loan portfolio, with the purpose to identify causes that create the increase of non-performing loans , especially in the microcredit retail fast credit, the analysis of the financial indicators was analyzed, surveys was applied with the members of the expired portfolio were carried out, interviews was made to Cooperative officials it was possible to determine which were variables that affect the non-performing portfolio, aspects that influence financial income, improve its results, project the financial institution towards a better performance, cost-effective and mainly to control and minimize the actual credit risk, the field research is one of the methods used in this project, because it is possible to propose solutions to the problem, as well as quantitative research because it is formal and qualitative research for making unstructured observations, open interviews, review of documents, Group discussion, evaluation of personal experiences. In addition, it was resorted bibliographical-documentary, the same one that was able to investigate, to know, to compare, to extend, and to reach a concrete knowledge of the different criterias and theories of diverse authors on the research. This inquiry has as result to establish several factors by which they influence in a direct way in the liquidity, so that it is causing the profit to be reduced by the provisions that must be made at the time of making accounting adjustments. The responsibility of the management and board of directors of “Santa Rosa de Patutan Ltda" Cooperative is to manage responsibly the money of the members and through financial intermediation to obtain sufficient income to cover the operational costs and also to obtain surplus profits that benefit its members and strengthen the patrimony of the cooperative.